Scientific Literacy: Sports Scientific Article Writing Training as an Effort to Increase Teachers' Professional Competence in Probolinggo Regency - Nur Muhammad, Heryanto; Anita Kumaat, Noortje; Wibowo, Sapto; Hidayat, Taufiq; Ahmad Arief, Nur; Wicahyani, Sri (Jurnal Abdimas, 2024)
Developing teacher professionalism is an important concern for the government as an education provider. Teachers have an important task and role, not only to provide scientific and technological information, but also to form attitudes and souls that are able to survive in the era of global competition among their students. Efforts to increase teacher professionalism are carried out through teacher certification programs, providing education and training for teachers, forming Focus Group Discussions in Teacher Working Groups and Subject Teacher Deliberations as well as always being productive in producing work in the field of education. One of the important self-development activities for teachers to participate in is related to writing scientific papers as a condition for employee promotion. The aim of this Community Service activity is to provide scientific literacy related to article writing as an effort to increase the professional competence of teachers in Probolinggo Regency. The methods used in this activity are workshops, offline and online training and assistance in completing tasks. Evaluation of the implementation of Community Service activity is based on filling out questionnaires by participants with an average score of 4.46 on a scale of 0-5. The result of this training is an increase in participants' knowledge of writing sports scientific articles.